2009
DOI: 10.1097/iop.0b013e3181b81e9f
|View full text |Cite
|
Sign up to set email alerts
|

Lacrimal Surgery Success After External Dacryocystorhinostomy: Functional and Anatomical Results Using Strict Outcome Criteria

Abstract: This study used strict criteria to assess functional and anatomical outcomes of primary ext-DCR and thus provide baseline measures of success with a minimal follow-up of 6 months. When canalicular disease was excluded, results for PANDO were higher. Surgery performed by the specialist lacrimal surgeon had higher success rates than when performed by trainee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 17 publications
4
39
0
4
Order By: Relevance
“…The other group included any patients who had a trainee operating on them (even if that was together with a consultant, n ¼ 26) and had a mean of 20.82 (95% CI: 9.12-32.54). This difference was not statistically significant (P ¼ 0.2199), similar to functional successes noted by Fayers et al 2 …”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…The other group included any patients who had a trainee operating on them (even if that was together with a consultant, n ¼ 26) and had a mean of 20.82 (95% CI: 9.12-32.54). This difference was not statistically significant (P ¼ 0.2199), similar to functional successes noted by Fayers et al 2 …”
Section: Resultssupporting
confidence: 69%
“…2,7,11 Our response rate of 38.7% was markedly lower than other postal questionnaire studies for OLR procedures 12,13 and most likely reflects our population of an inner city multi-cultural mix of patients, with 44% of the study population non-British. We found that the EE-DCR gave patients improvement in areas of general perception of well-being, including the social and psychological components contributing to health.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…19,20 It is now an established fact that, surgical expertise in the field of DCR surgery may dramatically affect the surgical outcome. 21 Both the primary ophthalmic and ENT surgeon in our study are well versed in the nasolacrimal anatomy and in performing high volume DCR surgeries. Thus, accountability of their surgical skill cannot become a questionable issue.…”
Section: 12mentioning
confidence: 99%
“…Postoperative soft tissue infections, previous trauma, and silicone tube intubation are other factors that have been attributed to failure. More recently, the frequency of entry into the ethmoidal sinus as opposed to the nose has been highlighted emphasising the importance of adequate knowledge of the nasal anatomy while performing external DCR [3,4,5,6,7,8]. Endoscopic transnasal DCR is a surgical innovation with an attempt to avoid these complications with similar or better results.…”
Section: Introductionmentioning
confidence: 99%